FINANCIAL RISK TOLERANCE AND INVESTMENT DECISIONS AMONGST SMES IN ZAMFARA STATE: THE MODERATING ROLE FINANCIAL LITERACY - Ibrahim Lawal; Habiba Ahmed Gwadabe; Adetokun Akeem Abiodun (Gusau Journal of Accounting and Finance)
Many small and medium enterprises in Zamfara State face difficulties turning their willingness to take financial risks into sound investment decisions. One key reason for this challenge is the low level of financial literacy among business owners. This study set out to examine how financial literacy shapes and strengthens the relationship between financial risk tolerance and investment behavior among small and medium enterprise owners in Zamfara State. A quantitative research approach was used, drawing on responses from selected business owners across all local government areas in the state. The study population included formally registered enterprises, and participants were chosen through a carefully structured sampling process that ensured fair representation across different business sectors. Data were gathered through a well-designed questionnaire that covered personal information, financial knowledge, willingness to take financial risks, and current investment practices. The questionnaire was administered both in person and through electronic means. The collected data were analyzed using statistical methods that allowed the researcher to test the relationship between the key variables. The findings revealed that both financial risk tolerance and financial literacy influence investment decisions, but the combination of the two had a much stronger impact. The study concludes that financial knowledge plays a vital role in helping business owners make smart, growth-oriented investments. It recommends that government and support agencies offer targeted financial education programs to improve investment outcomes for entrepreneurs in financially constrained environments.